Effect of Yellow Root Ethanol Extract (Fibraurea tinctoria Lour.) on Liver Histopathology of Paracetamol-Induced Male Swiss Webster Mice - Safari, Astina; Ramadhani, Juwita; Fauzi, Muhammad; Pratama, Rizki R. (Universitas Padjadjaran, Indonesia, 2025)
The public most commonly uses paracetamol, an analgesic antipyretic drug available over-the-counter without a doctor's prescription. The use of toxic doses can cause centrilobular necrosis, where paracetamol will form excessive N-acetyl-p-benzoquinone-imine (NAPQI), causing there to be insufficient glutathione to convert NAPQI into non-toxic compounds. The antioxidant activity of yellow root (Fibraurea tinctoria Lour.) can shield the liver from paracetamol-induced liver damage. This study aims to determine the hepatoprotective effect of an ethanol extract of yellow root (Fibraurea tinctoria Lour.) on the liver histopathology picture of mice (Mus muscular) induced by paracetamol. The study used 30 mice divided into six groups, namely healthy control (s), negative control (Nacmc), positive control (curcuma), treatment 1 given (75 mg/kg BW), treatment 2 (150 mg/Kg BW), and treatment 3 (300 mg/kg BW). Following a 7-day administration period, we initiated induction on the 8th day, and 24 hours later, we executed necropsy on all mice. Subsequently, we extracted their liver organs for histopathological preparations using hematoxylin eosin (HE) staining. The results showed that an ethanol extract of yellow roots (Fibraurea tinctoria Lour.) at a dose of 300 mg/kg BW had an effect on the histopathological picture of the liver of male Swiss Webster mice (Mus musculus) because it was able to maintain liver condition when given a dose of 300 mg/Kg BW.